Relevansi Pemikiran Ekonomi Islam Abu Ubaid Dengan Perekonomian Modern - Fitra Rizal (ACTIVA: Jurnal Ekonomi Syariah, 2018)
The history of Islamic economic thought dates back to the time of the Prophet Muhammad, namely when the al-Quran and al-Hadith were revealed. Muslim scholars basically try to develop Islamic concepts in accordance with the situation and conditions faced, while still relying on the al-Quran and al-Hadith. It must be admitted that the Muslim scholars of the past read a lot of the works of Greek and Roman thinkers, but they did not trace the writings, but deepened, developed, enriched and modified according to Islamic teachings. The Abu Ubaid Economic Outlook that is relevant to the modern economy includes; 1) International trade is trade between countries that cross the boundaries of a country. Long before the theory of international trade was found in the West, Islam had applied the concepts of international trade. Abu Ubaid has highlighted this, especially imports and exports. 2) International trade, international trade The idea of ​​Abu Ubaid on import export can be divided into three parts, namely: the existence of tariffs in international trade, excise of basic food ingredients is cheaper, and there are certain limits for excise tax. 3) The Function of Money, Abu Ubaid acknowledges the existence of two functions of money, namely as a standard of exchange rates and exchange media. Keywords: Abu Ubaid,Islam economic, modern economic